A Decadal Analysis of Trends and Patterns in Student Enrollment across Academic Programs of San Sebastian College-Recoletos De Cavite - Tommy Ditucalan (JPAIR)
This study examines enrollment patterns of students at San Sebastian College-Recoletos de Cavite across its various academic programs from 2014 and 2023. Given the critical role that higher education plays in society’s progress, effective strategic planning requires a thorough understanding of enrollment dynamics. The study uses a quantitative methodology to examine an extensive dataset that was compiled from official enrollment records, with ethical considerations guiding data confidentiality. The results highlight the complex relationship between program popularity and the changing job market by revealing complicated enrollment patterns. Key findings include variations in programs such as AB Communication and BS Electronics Engineering, a growing interest in BS Nursing and BS Criminology, and a continued demand for BS Information Technology. Administrators are guided by these insights while making strategic decisions, allocating resources, and developing programs. The study provides SSC-RdC with a framework for understanding the complicated world of higher education. It recommends developing programs strategically, allocating resources where they are required, engaging in targeted marketing, and regularly assessing whether adjustments are necessary. In conclusion, this study provides valuable insights not only for SSC-RdC but also for the broader context of higher education. The intention is to assist educators and school administrators at SSC-RdC in enhancing their curricula for long-term growth and success.